The Role of Digital Mindset in Mediating the Relationship Between Dynamic Managerial Capabilities and Strategic Leadership in Indonesian Startups - Vincentia Heryani Septyaningrum; Siti Aulia Chairunisa; Dony Nickolas (Institut Agama Islam Sunan Giri Ponorogo, 2026)
High failure rates among Indonesian startups often stem from weak strategic planning and an inability to navigate rapid technological shifts. This study investigates the mediating role of a digital mindset in the relationship between dynamic managerial capabilities and strategic leadership. A quantitative explanatory design was employed, utilizing data from 100 startup managers collected via LinkedIn and Google Forms. Analysis using multiple regression and the PROCESS Macro reveals that while dynamic managerial capabilities do not directly impact strategic leadership significantly, they exert a profound influence on developing a digital mindset. Digital mindset serves as a full mediator, effectively translating managerial resources into impactful leadership behaviors and explaining 50.9% of the variation in strategic leadership. These findings contribute to the Upper Echelons Theory by highlighting that managerial skills in the digital era remain latent unless filtered through a technology-oriented cognitive framework. Practical results offer a roadmap for founders to prioritize mental adaptability and digital experimentation to ensure long-term organizational sustainability